ORGANIZING PHYSICAL EDUCATION OF STUDENTS WITH DISABILITIES WITHIN THE SPECIFIC TEST REQUIREMENTS - Niyozmatov Elbek Rustamalievich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
In this article, the pedagogical and psychological aspects of organizing the physical education of students with disabilities and disabilities based on the requirements of the special test “Alpomish and Barchinoy” are studied.